Pengaruh Penggunaan Ankle Foot Orthosis Dinamis Terhadap Kecepatan Jalan Pada Anak Penderita Cerebral Palsy - Cica Trimandasari M; Sri Surini Pudjiastuti (Poltekkes Kemenkes Surakarta, 2019)
Background: cerebral palsy is a non-progressive motor disorder that causes limited activity, paralysis, inability to control motion and is often accompanied by cognitive impairment or visual deficits.Children who experience cerebral palsy will definitely have limitations in the process of mobility. To help limitation of activity that occurs in children with cerebral palsy, ankle foot orthosis is used. Ankle foot orthosis is expected to help the patient in performing his activities at all times to give effect on the walking speed. In this research, actions performed by taking data before and after using dynamic ankle foot orthosis. Purpose of this research to determine the effect of the use of dynamic ankle foot orthosis on walking speed ​​in children with cerebral palsy